1989
DOI: 10.1111/j.1442-9993.1989.tb01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Species‐richness and soil phosphorus in plant communities in coastal New South Wales

Abstract: Species-richness (recorded as number of species in 16 m-' quadrats), in more than 60 coastal sites developed over various substrata, exhibited a significant non-linear relationship with soil total phosphorus extracted from associated soil samples. Although the general form of this relationship is not incompatible with a resource cotnpetition model, the significant proportion of the total variance accounted for by the species-richness/phosphorus relationship suggests that a more detailed examination of phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
4
15
0
Order By: Relevance
“…3a). A similar dependence of plant distribution and species diversity on soil P levels has been found before (Adam et al 1989;Beadle 1962Beadle , 1966Huston 1980). Preliminary analysis of plant alpha diversity and mineral nutrition strategies in south-western Australia suggests that a relatively high proportion of species are non-mycorrhizal (Brundrett 2009;Lambers et al 2008b).…”
Section: N or P Limitation In Ocbils?mentioning
confidence: 70%
“…3a). A similar dependence of plant distribution and species diversity on soil P levels has been found before (Adam et al 1989;Beadle 1962Beadle , 1966Huston 1980). Preliminary analysis of plant alpha diversity and mineral nutrition strategies in south-western Australia suggests that a relatively high proportion of species are non-mycorrhizal (Brundrett 2009;Lambers et al 2008b).…”
Section: N or P Limitation In Ocbils?mentioning
confidence: 70%
“…Previous studies in the central coastal region of New South Wales have found correlations between vegetation and nutrients, particularly phosphorus (Beadle 1953(Beadle , 1954McColl & Humphreys 1967;Adam et al 1989) and nitrogen (Hannon 1956;McColl & Humphreys 1967); however, few studies have recognized complex environmental gradients involving a number of environmental factors. Complex environmental gradients have been found in many other areas in Australia (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Rice and Westoby (1983) also postulated that soil nutrients could be one of the main determinants of patterns in species richness in sclerophyll communities of eastem Australia. Adam et al, (1989) showed a strong relationship between soil phosphorus and species richness in coastal plant communities from a range of substrata in eastem New South Wales. This has led to the general acceptance of a 'nutrient' hypothesis regarding the distribution of plant species.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, although Specht (1988b) showed a positive relationship between site productivity and species richness on a regional scale, both theory (Grime 1979) and observational studies (e.g. Adam et al, 1989) suggest that relationships at more local scales can be variable.…”
Section: Vegetationmentioning
confidence: 95%